Analisis produktivitas dan pengaruhnya terhadap pendapatan pemilik usaha industri kecil batu bata di Kecamatan Bajubang Kabupaten Batang Hari - Sari, Intania Novita; Heriberta, Heriberta; Parmadi, Parmadi (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2024)
This research aims to analyze 1) productivity of business production factors in the small brick industry in Bajubang District, Batang Hari Regency  2) determine the effect of capital productivity, labor productivity, and raw material productivity on the income of brick business owners in Bajubang District, Batang Hari Regency. The analytical tool used is quantitative descriptive analysis using multiple linear regression. Based on the social and economic characteristics of brick industry owners in Bajubang District, it can be concluded that the average age is 47 years, the majority are male, with an elementary school/equivalent education level, and the average number of dependents is 5 people. The results of multiple regression analysis in this research show that the variables capital productivity, labor productivity and raw material productivity have a significant effect on the income of brick industry owners in Bajubang District, Batang Hari Regency.